Evaluation of the effect of intrathecal clonidine to decrease shoulder tip pain in laparoscopy under spinal anaesthesia - Ghodki, Poonam S (Medknow Publications, 2010)
Sixty ASA grade I/II patients scheduled for elective short laparoscopic procedures under spinal anaesthesia were divided into two groups of 30 each. The first group (group C) received 3.5 ml of hyperbaric bupivacaine with 30 mcg of clonidine. The second group (group B) received plain bupivacaine 3.5 ml. Till date, the limiting factor for use of spinal anaesthesia for laparoscopy was patient’s discomfort due to shoulder tip pain. From our study it can be concluded that bupivacaine along with clonidine in low doses provides good sedation and analgesia in intraoperative and post-operative period and at the same time abolishes shoulder tip pain during laparoscopic procedures. In addition, no significant changes in haemodynamics occur with the low dose of clonidine used.